Pengaruh Kondisi Geomorfologi Terhadap Penggunaan Sumber Daya Lahan Dan Aktivitas Masyarakat Desa Margaluyu, Kecamatan Pangalengan - Atmina Lufi Amadia; Sarah Safa Mutmainnah; Anisa Nurhidayati; Muthia Gusti Amelia (Lembaga Pengembangan Kinerja Dosen, 2024)
Land, or soil, is the part of the earth's surface that can be used by humans for survival. Land is the terrain on the earth's surface and includes solid, liquid and gas. Things that affect land use are climate, relief, hydrology, vegetation, animals and the consequences of past and present human activities. land use is the process of utilizing land gradually to obtain results and to increase land use value without changing the physical form of land. Margaluyu Village has diverse geomorphological conditions, with vegetation dominated by tea gardens and pine forests that function as water catchment areas. This greatly influences the work of the surrounding community, which is generally as farmers and gardeners. the gardens that are there are chilies, corn, tomatoes, cabbage, coffee, tea and oranges. Margaluyu Village has Situ Cipanunjang, which is sometimes used as a training ground for national athletes in rowing, as well as tourism sectors such as Situ Cileunca, Situ Cipanunjang and Taman Bukit Bintang.